Entrepreneur's Toolkit: tools and techniques to launch and grow your new business - Harvard Business (ed.) (Boston : Harvard Business School Press, 2004)
Business
Keywords: Entrepreneur's Toolkit; Entrepreneur; Business; Self-Diognosis; partenrship; corporation; Business plan; financing ; enterprise growth; harvest time going public